Determinant of Latent Pulmonary Tuberculosis Incidence among Health Workers in Community Health Centers in Surabaya, Indonesia - Andajani, Susilowati (Folia Medica Indonesiana, 2019)
About 2 billion people in the world are infected with latent TB, and 5-10% of them will develop into active TB. The purpose of this study was to analyze the relationship between nutritional status, behavior, duration of work, comorbidities, and workplace ventilation with the incidence of latent pulmonary TB. This type of research is an observational cross sectional analytic, a sample of research of poly TB analysts and nurses from 13 health centers in Surabaya, a sample of 30 people. Statistical analysis with Chi Square and t-2 test samples were free with a=0.05. The results of this study are: The proportion of latent TB incidence is (46.70%) and 85.71% of them are women. None of the respondents detected DM, and none of the history had HIV, silicosis or hepatitis. All workplace ventilation is not good. There was no relationship between nutritional status, behavior, duration of work and the incidence of latent pulmonary TB. The conclusions from the study are, 1) The proportion of health center health workers affected by latent pulmonary TB infection is 46.70%, 2) There is no relationship between nutritional status, length of work, and behavior of health center health workers in Surabaya with latent pulmonary TB incidence. The highest incidence of latent pulmonary TB occurred in those with a working period of five years or more, with the highest education in D3 medical analysts/akper. All workplace ventilation is not good. The highest incidence of latent pulmonary TB (42.86%) in employees at the PRM Health Center (microscopic referral health center).